Public-Management Activities in the Judicial Authorities of Ukraine in the Context of Increasing the Level of Public Confidence - КornevaOlha (Theory and Practice of Public Administration, 2023)
The article reveals the peculiarities of public-management activities in the system of judicial authorities of Ukraine. It has been established that these activities are implemented by various entities, which include court administration staff; staff of the State Judicial Administration of Ukraine and its territorial departments; the Court Security Service; staff of the Higher Qualification Commission of Ukraine; the National School of Judges of Ukraine, etc. Grouping of factors that affect the vectors of the development of public-management activities in the judicial authorities of Ukraine under the conditions of martial law has been carried out. Two groups of factors have been distinguished: principal and non-principal. The main role of public-management activities in the judicial authorities is to ensure functioning of the institutional bodies of the judicial authorities and implementation of the mechanisms of the state to establish the supremacy of law. Dependence of public-management activities in judicial authorities on the effectiveness of the public management system as a whole has been established. Highlighting the principal factors, the article emphasizes that the effectiveness of public-management activities of judicial authorities depends on: 1) the effectiveness of the European principles of good governance implementation; 2) increasing public confidence in judicial authorities; 3) digitization of the administrative processes in courts; 4) overcoming the consequences of hostilities in de-occupied territories and restoring the system of justice. Non-principal factors have been identified, the list of which can be continued. These include: 1) sufficient financing of judicial authorities’ bodies, institutions and agencies; 2) sufficient staffing of court administration and bodies, institutions and agencies of judicial authorities with managers; 3) the level of remuneration of the court administration staff as well as bodies, institutions and agencies of the judicial authorities; 4) updating the organizational and legal principles of public-management activities in judicial authorities; 5) updating the communicative relations of the court staff and other judicial authorities with the media, individuals and legal entities; 6) access to justice for the disabled and other people with limited mobility; 7) improvement of the document circulation system in courts and bodies of justice; 8) strengthening of control over public-management activities in judicial authorities.